2019
DOI: 10.1002/kjm2.12064
|View full text |Cite
|
Sign up to set email alerts
|

Steroid withdrawal or avoidance is safe in high‐risk kidney transplants: A systematic review and meta‐analysis

Abstract: The present study is aimed to assess the safety and efficacy of steroid withdrawal or avoidance (SWA) in high‐risk kidney transplant (HRKT). We performed a systematic review of the literature and pooled analysis of the available data concerning SWA following HRKT. HRKT is associated with patients undergoing repeat kidney transplantation, in African American recipients, or in patients with panel‐reactive antibody levels >20%. Seven cohort studies and one randomized controlled trial, involving a total of 22 075 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The absorption band is in conjugated diene absorption in the transition π → π * in the area ≥ 270 nm. This shows the double bond in the conjugated flavonoid powder [12]. The addition of NaOH shear reactor causes a shift in wavelength to show the presence of OH on ring B [14] anthocyanin and anthocyanidin compounds will decompose with the addition of NaOH.…”
Section: Characterizationmentioning
confidence: 97%
“…The absorption band is in conjugated diene absorption in the transition π → π * in the area ≥ 270 nm. This shows the double bond in the conjugated flavonoid powder [12]. The addition of NaOH shear reactor causes a shift in wavelength to show the presence of OH on ring B [14] anthocyanin and anthocyanidin compounds will decompose with the addition of NaOH.…”
Section: Characterizationmentioning
confidence: 97%
“…However, a recent meta-analysis reported results in favor of steroid discontinuation even in subjects considered to be at high immunological risk. 26 GN-IgA is also considered as a contraindication to the steroid discontinuation. An association was reported between steroid discontinuation and an increased risk of GN-IgA recurrence.…”
Section: The Toxicity Of Corticosteroidsmentioning
confidence: 99%
“…Steroid withdrawal was initiated within 1 wk after transplantation in many of these patients. Based on this meta-analysis, steroid withdrawal within 1 wk after transplantation was associated with significant reduced risk of patient death[ 10 ].…”
Section: Transplant Recipientsmentioning
confidence: 99%
“…Although other components of the immunosuppressive regimen, such as the type of CNI (tacrolimus vs cyclosporine A), can affect PTDM risk, as in the multivariate analysis of Tillmann et al ’s[ 108 ] study showed higher risk of prediabetes with long-term low-dose steroid, independent of the higher risk of tacrolimus inducing PTDM compared with cyclosporine. On the other hand, a meta-analysis on more than 22000 kidney transplant patients found that early steroid withdrawal during 1 wk after transplantation is associated with less PTDM risk (RR: 0.91; 95%CI: 0.37-0.97; P = 0.04)[ 10 ]. Association between new-onset hyperglycemia and GC-containing maintenance immunosuppression among liver transplant recipients is controversial[ 109 , 110 ].…”
Section: Side Effectsmentioning
confidence: 99%